A basic study for application of laser peening to large-scale steel structure. Issue 1 (2nd January 2016) - Sakino, Yoshihiro; Yoshikawa, Kenji; Sano, Yuji; Sumiya, Rie; Kim, You-Chul
Abstract : Laser peening can introduce compressive residual stress to the surface and therefore is effective in enhancing fatigue strength. In this study, we conducted laser peening in air with a water film formed by a nozzle and examined whether the distribution of residual stress along the thickness was different from that achieved by laser peening in water in our previous studies. We also assessed the resultant residual stress and fatigue life when the pulse energy was reduced for developing a simple method to conduct laser peening on large structures. Compressive residual stress equivalent to that observed after laser peening in water was obtained in nozzle-type laser peening in terms of magnitude and depth. With the reduction of pulse energy, it was observed that the depth of the compressive residual stress tended to decrease significantly and the fatigue life also tended to reduce. The results indicate that the depth of the compressive residual stress has a considerable effect on the fatigue life of welded structures as well as the magnitude of the surface residual stress.